Effectiveness of educational intervention in improving medication adherence among patients with diabetes in Klang Valley, Malaysia - Atolagbe, Emmanuel Timilehin; Sivanandy, Palanisamy; Ingle, Pravinkumar Vishwanath (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background The diabetes patients’ adherence to prescription medication is 67.5%, which is lower than that of patients with any other medical conditions. Patients with low medication adherence are more likely to experience clinical complications, repeated hospitalizations, increased mortality, and increased healthcare costs, hence, education on disease and medication adherence is vital now. This study aimed to assess the level of medication adherence, medicine and information-seeking behaviour, and the effectiveness of online educational intervention in improving medication adherence and medicine and information-seeking behaviours among patients with diabetes in Klang Valley, Malaysia. Methods Individuals aged 12 years and above with a prior diagnosis of diabetes were identified and randomly divided into (control (n=183), and intervention groups (n = 206). Data about their medication adherence and information-seeking behaviour were obtained. As part of the online educational intervention, a month of daily general reminders to take their medications and educational materials about diabetes had provided to them via WhatsApp groups. After a month, the groups were reassessed, and the data were compared. Results The results showed that, at baseline, most of the respondents in the control (58.8% females and 53.08% males) and intervention (65.52% females and 85.12% males) groups had a low level of medication adherence. After a month of intervention, medication adherence was significantly improved in the intervention group (91.4% females and 71.28% males) compared to the control group (38.23% females and 44.44% males). At baseline, only 96 (52.45%) respondents in the control group and 110 (52.38%) in the intervention group preferred to read online educational materials to know more about their condition(s), it was improved after a month of intervention in the intervention group where 204 (99.02%) respondents prefer online materials, however no change in the control group response. Conclusion The study concludes that medication adherence and information-seeking behaviours among the study population have been significantly improved after a month of structured intervention. Medication adherence plays a crucial role in risk reduction strategies subsequently it improves the patient’s quality of life. Thus, well-planned more robust educational interventions on chronic diseases are warranted to improve the health outcomes of the patients.